Knowledge, attitudes, and practices regarding use of malaria prevention measures among pregnant women in Busia County, Kenya - Sudoi, Raymond; Onono, Maricianah; Nyaberi, Jackline (American Journal of Social Sciences and Humanities, 2025)
Malaria poses severe health risks for pregnant women in Sub-Saharan Africa, especially in Kenya, where it remains a leading cause of morbidity and mortality. Despite the availability of Insecticide-Treated Nets (ITNs) and Intermittent Preventive Treatment in pregnancy (IPTp), utilization remains low, necessitating studies on Knowledge, Attitudes, and Practices (KAP) to inform effective interventions. In a parallel-group randomized trial (September 2023 to February 2024), 156 pregnant women aged 15–49 in Busia County were block-randomized to receive either SMS reminders on ITN and IPTp use (intervention group) or no reminders (control group). Primary outcomes were ITN utilization and IPTp adherence. Using a structured questionnaire, a KAP assessment was conducted regarding ITNs and IPTp for malaria prevention. Ethical approval was obtained, and informed consent was secured from all the participants. Healthcare providers and Community Health Workers (CHWs) were key information sources at baseline; post-intervention, SMS reminders became significant in the intervention group (46%). ITN use remained high across both groups, while IPTp recall, and adherence improved. Positive attitudes (>90%) and high perceived severity (94%-98%) persisted. Post-intervention, the intervention group showed greater perceived benefits (19% vs. 8%, p=0.018), and self-efficacy remained high, supporting SMS feasibility and acceptability. Strong adherence to ITN and IPTp use was driven by high perceptions of malaria’s severity and the benefits of preventive measures, underscoring the importance of ongoing education.Combining CHW education with SMS reminders may enhance malaria prevention in pregnant women, supporting sustained practices and improving maternal and infant health in high-risk areas.